Challenges involved in the Salmonella Saintpaul outbreak and lessons learned - Taylor, Ethel; Kastner, Justin; Renter, David G. (My University, 2010)
A 2008 multistate foodborne outbreak of Salmonella Saintpaul caused more than 1,400 illnesses in the United States (U.S.). Although initial investigations suggested tomatoes as the potential vehicle, jalapeño and serrano peppers were subsequently found positive for the outbreak strain. The uncertainty associated with this incident caused government, industry, and the public to question the efficacy of the U.S. food safety system. Examination of the response to this incident exposed breakdowns in several areas. Communication at all levels was lacking, leading to an absence of coordinated actions and conflicting risk communication messages. Variations in resources between local and state health departments created delays in gathering accurate information for epidemiological investigations. Although new laws required increased documentation, rapid and thorough traceback of produce products remained elusive. Three factors contributed to the difficulty in the Salmonella Saintpaul outbreak, including (1) delayed response due to discrepancies in available resources and expertise at state and local levels, (2) inadequate communication between stakeholders and agencies, and (3) poor traceability capabilities. Future responses to foodborne illness outbreaks may be improved by addressing these three factors.
Keywords: Food safety; Produce; Outbreak; Salmonella; Salmonella Saintpaul